Banking consolidation. Challenges and prospects - Novickyte, Lina; Jasienė, Meilutė (Konsolidacja systemu bankowego. Wyzwania i perspektywy, 2011)
The recent financial turmoil has prompted to review the current financial regulatory framework mechanism. The present financial system reform could be a cause of the integration and consolidation processes in banking. This article examines the European Union’s financial system changes, regulatory rules, and the extending potential of the financial sector. This paper attempts to evaluate the European Union structural changes in the banking sector and identify the determinants of these changes. The banking sector having to vary among the three major activities – profitability, liquidity, and safety – should ensure an adequate return for its shareholders and contribute to a stable financial system
Ekonomia = Economics, 2011, Nr 2 (14), s. 244-253
Keywords: M&A; consolidation; financial stability; banking regulation